Dynamics and capture of space-charge dominated electron beams in crossed-fields system - Agafonov, A.V. (Вопросы атомной науки и техники, 1999)
Problems of nonlinear dynamics of space-charge dominated electron beams in crossed ExB-fields are discussed from the point of view of the investigation of schemes of intense electron beam formation for compact cyclic accelerators and for high-efficiency relativistic magnetrons. The review of the results of computer simulations of an electron clouds formation due to nonlinear azimuthal instability inside magnetron is given. A scheme of electron storage and capture of electron beams in crossed fields is proposed.